2014
DOI: 10.5758/vsi.2014.30.4.113
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Methylenetetrahydrofolate Reductase Mutations and Plasma Homocysteine Levels in Patients with Thromboembolic Occlusion

Abstract: Purpose:Hyperhomocysteinemia has been identified as an independent risk factor in arterial and venous thrombosis. Mutations in genes encoding methylenetetrahydrofolate reductase (MTHFR), involved in the metabolism of homocysteine, may account for reduced enzyme activity and elevated plasma homocysteine levels. In this study, we investigated the interrelation of MTHFR C677T genotype and level of homocysteine in patients with arterial and venous thrombosis.Materials and Methods:We retrospectively reviewed the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 26 publications
2
28
0
2
Order By: Relevance
“…It has also been reported to take part in the initiation and maintenance of a migraine episode via endothelial cell injury, induction of trigeminal and cortical excitability, direct neurotoxic effects, and malfunction in blood coagulation system . As one of the key enzymes in folic acid and the Hcy metabolism, MTHFR takes charge of the irreversible transformation of 5,10‐methylentetrahydrofolate to 5‐methyltetrahydrofolate, a methyl donor for methylation of Hcy to methionine . Several polymorphic sites have been found in MTHFR gene, but only the C677T (Ala > Val, rs1801133) and A1298C (Glu > Ala, rs1801131) substitutions may lead to hyperhomocysteinemia due to the reduction of enzymatic activity .…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported to take part in the initiation and maintenance of a migraine episode via endothelial cell injury, induction of trigeminal and cortical excitability, direct neurotoxic effects, and malfunction in blood coagulation system . As one of the key enzymes in folic acid and the Hcy metabolism, MTHFR takes charge of the irreversible transformation of 5,10‐methylentetrahydrofolate to 5‐methyltetrahydrofolate, a methyl donor for methylation of Hcy to methionine . Several polymorphic sites have been found in MTHFR gene, but only the C677T (Ala > Val, rs1801133) and A1298C (Glu > Ala, rs1801131) substitutions may lead to hyperhomocysteinemia due to the reduction of enzymatic activity .…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are reports that have linked rs1801133 polymorphism within MTHFR gene with arterial hypertension [33], cancer [34], diabetes [35], and many other diseases; however, the results of replication studies vary in between [36]. The homozygous mutated subjects for rs1801133 have higher homocysteine levels and hyperhomocysteinemia is an emerging risk factor for various thrombotic diseases [37]. A large number of studies has clearly shown that MTHFR gene polymorphism rs1801133 is a risk factor for thrombotic events [25].…”
Section: Discussionmentioning
confidence: 99%
“…Increased homocysteine levels are known risk factors for cardiovascular diseases and formation of thrombosis (24). Deficiencies of group B vitamins (B6, folic acid, B12) and genetic deficiency of MTFHR enzyme which is involved in transformation of folate to its active form are risk factors for hyperhomocysteinemia (25). Especially two known polymorphisms of the MTFHR gene (MTFHR C677T and A1298C) have been associated with increased homocysteine levels (26).…”
Section: Discussionmentioning
confidence: 99%
“…Especially two known polymorphisms of the MTFHR gene (MTFHR C677T and A1298C) have been associated with increased homocysteine levels (26). However, a direct relation of gene mutations with thrombosis has not been demonstrated, although it is known that MTFHR gene mutations are a reason for hyperhomocysteinemia and hyperhomocysteinemia is a risk factor for formation of thrombosis (25).…”
Section: Discussionmentioning
confidence: 99%